2016
DOI: 10.1136/bjsports-2015-095771
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical therapy treatment of clearly defined subacromial pain: a systematic review of randomised controlled trials

Abstract: Exercise therapy should be the first-line treatment to improve pain, function and range of motion. The addition of mobilisations to exercises may accelerate reduction of pain in the short term. Low-level laser therapy, PEMF and taping should not be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 98 publications
(129 reference statements)
4
72
0
6
Order By: Relevance
“…This might be because previous reviews have included fewer studies, 13 and have not performed a meta-analysis and probably based their statements of evidence on non-significance of the individual trials. 57 Our results for ultrasound therapy, hyaluronate, tape, pulsed electromagnetic field therapy, ECSWT, microwave and platelet-rich plasma support previous reviews. 11 13 …”
Section: Comparisons With Other Studiessupporting
confidence: 86%
“…This might be because previous reviews have included fewer studies, 13 and have not performed a meta-analysis and probably based their statements of evidence on non-significance of the individual trials. 57 Our results for ultrasound therapy, hyaluronate, tape, pulsed electromagnetic field therapy, ECSWT, microwave and platelet-rich plasma support previous reviews. 11 13 …”
Section: Comparisons With Other Studiessupporting
confidence: 86%
“…short wave diathermy [SWD]) and microwave diathermy were modalities commonly used in the physical therapy profession in the management of painful musculoskeletal conditions during the 1900s. The lack of rigorous scientific evidence to support effectiveness in comparison to exercise or placebo groups (Akyol et al, 2010;Haik et al, 2016;Kroeling et al, 2013;Page et al, 2014Page et al, , 2016, the dated nature of clinical evidence, and concerns regarding safety, have led to such modalities being excluded from many physical therapy entry-level curricula in some countries. Physical therapy is not yet a profession recognized by the Chinese government; and rehabilitation work in China is led by rehabilitation medicine practitioners, assisted by rehabilitation therapists.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of 64 randomized controlled trials (RCTs) investigating the effect of physical therapy on individuals with SSI (Haik, Alburquerque-Sendin, Moreira, Pires, & Carmargo, 2016) reported that all studies measured subjective outcomes of pain and function and only 15 included an objective outcome measure, being active shoulder flexion, and abduction range.…”
Section: Introductionmentioning
confidence: 99%
“…No previous study has investigated the effect of physiotherapy interventions that increase thoracic range of motion or increase posterior shoulder range (Dickens, Williams, & Bhamra, 2005;Haik et al, 2016;Kromer et al, 2013). Common clinical physiotherapy techniques used to increase thoracic range of motion include central posteroanterior, unilateral posteroanterior, and transverse accessory mobilizations to the spine, as well as accessory mobilization of the ribs due to their strong attachment to the thoracic spine (Edmondston et al, 2007;Exelby, 2011).…”
Section: Introductionmentioning
confidence: 99%